A Retrospective Analysis of the Treatment of Cesarean Scar Pregnancy by High-Intensity Focused Ultrasound, Uterine Artery Embolization and Surgery - Fang, Shanyu; Zhang, Ping; Zhu, Yuanfang; Wang, Fen; He, Linsheng (Frontiers in Surgery, 2020)
Objective: This study aims to retrospectively analyze the clinical curative effects of surgery, uterine artery embolization (UAE), and high-intensity focused ultrasound (HIFU), in order to provide the theory and evidences for selecting the optimal treatment for caesarean scar pregnancy (CSP). Methods: Women with CSP were treated with surgery (laparoscopic, hysteroscopy, and hysteroscopy-laparoscopic surgery) for clearance of focal lesion, UAE combined with curettage, and HIFU combined with curettage. The general conditions and therapeutic effects, including vital signs during the operation, discomfort of discharge, cure rate, total blood loss, decline in the rate of hCG and hospital stay, were compared and analyzed. Results: For the 154 CSP patients, the cure rate of surgery (n=95) was 97.89%, the cure rate of UAE (n=32) was 43.74%, and the cure rate of HIFU (n=27) was 70.37%. The difference was statistically significant (P<0.05). Furthermore, the hCG level of surgical patients quickly declined, while HIFU slowly declined. The difference between the decline rate of hCG and mean hospitalization time was statistically significant (P<0.05). Conclusion: CSP patients with <55 days of gestational age and a <30 mm gestational sac can be treated with surgery, UAE and HIFU, and achieve safe and effective therapeutic effects.